Trauma Care in Angola: Highlights and Strategic Insights from the 2nd Angolan Trauma Surgery Congress - Márcio Teodoro da Costa Gaspar; Paulo Campos; Nuno Sevivas; João Maia Teixeira; Rodrigues Leonardo; Agostinho Matamba; Pedro Henrique Ferreira Alves; Matchecane Tlhomulo; Adilson Oliveira; João Abreu; Maricê Castro; Roseny Rodrigues; et al. (Surgery in Practice and Science)
The 2nd Angolan Trauma Surgery Congress, held in Luanda, brought together healthcare professionals, surgeons, and policymakers to address the pressing challenges in trauma care across Angola. This article summarizes the congress’s key themes, clinical insights, and policy discussions, with an emphasis on improving trauma systems, multidisciplinary coordination, and evidence-based surgical practices. The sessions underscored the urgent need for capacity building, trauma registries, and the standardization of pre-hospital and hospital-based trauma care protocols. The discussions also provided a platform for evaluating Angola’s current surgical response to polytrauma, highlighting advances, limitations, and future directions.